Development of an Edpuzzle-Based Learning Video on the Human Digestive System to Enhance Conceptual Understanding among Eleventh-Grade High School Students - Rahma, Alya; Rohani (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to develop an Edpuzzle-based instructional video on the human digestive system and evaluate its validity, practicality, and effectiveness in improving students’ conceptual understanding. This research employed a Research and Development (R&D) approach using the 4D development model, consisting of Define, Design, Develop, and Disseminate stages. The participants were 25 eleventh-grade students at SMA Negeri 7 Medan. The research instruments included expert validation sheets, teacher and student response questionnaires, and essay tests in the form of pre-tests and post-tests based on Anderson and Krathwohl’s indicators of conceptual understanding, including interpreting, exemplifying, classifying, summarizing, inferring, comparing, and explaining. Data were analyzed through validity, practicality, and effectiveness assessments using percentage analysis and N-Gain calculations. The results showed that the Edpuzzle-based instructional video was categorized as highly valid, with validation scores of 98.75% from media experts, 96.25% from material experts, and 94% from assessment experts. The practicality assessment indicated that the developed media was highly practical, with scores of 97.50% based on teacher responses and 98.33% based on student responses. Furthermore, the effectiveness analysis demonstrated an improvement in students’ conceptual understanding, with the average score increasing from 49.52 on the pre-test to 86.04 on the post-test and an N-Gain value of 0.72, categorized as high. Therefore, the Edpuzzle-based instructional video developed in this study is a valid, practical, and effective learning medium that can support students’ conceptual understanding of the human digestive system and provide an innovative alternative for Biology learning in accordance with the needs of modern education.